EDUCATIONAL SIGNIFICANCE OF ISLAMIC SPIRITUALITY - Zokirova Ra’no Islom qizi (Journals Park Publishing, 2025)
In its domestic and foreign policy, Uzbekistan pays great attention to universal values expressed in the shell of Islam and attaches an important place to them. This is due to the fact that the religion of Islam and its values play an important role in the formation of the material and spiritual life of our people, turning our country into a major place of world culture. These aspects determine the important tasks of studying the history of national ideas. "In our country, on the basis of the noble idea of 'enlightenment against ignorance', the promotion of the humanistic essence of Islam and its service to noble goals such as peace and friendship will remain one of the constant issues on our agenda."
Keywords: History of the national idea, in Central Asia during this period, religious and secular sciences, spirituality, spiritual education, spiritual value, protective order, neighborhood, socio-spiritual environment, public control.